Gestion De Credito Y Cobranza Del Centro Comercal Torres - Mera Jimenez, Milton Omar (2018)
Organizations today face a series of problems in relation to their finances, mainly in the administration of their resources, by their nature and their structure requires their different functional areas such as administration, marketing, accounting, costs, finance, credit and collections; performance with efficiency and effectiveness. (Arturo, 2014). The policy of the commercial company "Torres" is to market items for the home, of high quality and with affordable prices to the different economic estates, seeking to satisfy the needs and expectations of customers and seek to lead sales at the local and provincial levels. Among the aspects to consider is whether its sales capacity is ideal, its efficient credit system and recovery of collections is fast, how much time is lost for customers to pay, the requirements to endorse the prospectus of the company are known in the company. client in his credit capacity to fulfill obligations. The granting of credit allows a company to substantially increase its sales, considering that customers prefer to make purchases to pay in small installments within a reasonably determined period, that is why credit is a mechanism par excellence that increases their sales. In the commercial environment and its economic system, money is the main axis that gives the turn to the company, instead the credit comes to be a promise of payment that includes interest, but in a broad way, the credit today comes to replace money since people use it to buy a good (Russia, 2011). The binomial credit - collections, provides companies with the necessary tools to increase sales and revenues in their financial cycles, so it is essential to develop the granting of loans, it is necessary that they are first accurate in their granting and that their recovery be feasible Also the second part of this binomial is collections, the work of the administrators must be in a way that does not hurt the commercial relationship with the client.